Key words in science & technology - Mascull, Bill (HarperCollin Publishers, 1997)
This book analyses and explains the vocabulary of science and technology and develops your ability to understand it and use it effectively. Each vocabulary is introduced its meanings, how it is used and how words relate to each other.